Antimony in urine during early pregnancy correlates with increased risk of gestational diabetes mellitus: A prospective cohort study. (February 2019) - Zhang, Guofu; Wang, Xiaoyi; Zhang, Xu; Li, Qian; Xu, Shangzhi; Huang, Li; Zhang, Yu; Lin, Lixia; Gao, Duan; Wu, Meng; Sun, Guoqiang; Song, Yang; et al.
Abstract: Background: Antimony (Sb) has been associated with type 2 diabetes in previous studies. However, the role of Sb in the incidence of Gestational diabetes mellitus (GDM) remains unclear. Objectives: We investigated the association between Sb exposure during early pregnancy and the risk of GDM. Methods: We performed a prospective study of 2093 pregnant women from the Tongji Maternal and Child Health Cohort (TMCHC). Sb concentrations were measured in urine samples during early pregnancy by ICP-MS. The association between urinary Sb concentration and GDM incidence was assessed using robust Poisson regression model after adjustment for confounders. Results: The 95th percentile value of creatinine-corrected Sb (CC-Sb) concentration in the urine of all pregnant women was 1.33 μg/g. The CC-Sb concentrations were significantly higher in women with GDM than those without GDM (median value: 0.49 μg/g vs. 0.38 μg/g, p  = 0.001). After adjustment for potential confounders, for each one natural logarithmic unit increase in Sb concentration, there was 29% [adjusted relative risk (RR) = 1.29; 95% confidence interval (CI): 1.06, 1.57] increase in the risk of GDM. Women in the highest tertile for CC-Sb had a 1.92-fold (95% CI: 1.42, 2.60) higher risk of GDM compared with women in the lowest tertile ( p -value for trend <0.001). Conclusion: To our knowledge, this is the first research of an association between urinary Sb levels during pregnancy and GDM. Our study suggests that pregnant women with higher Sb exposure levels may have a higher risk of GDM and this association remains consistent even after stratification. Highlights: The first prospective study to investigate the relationship between antimony and gestational diabetes mellitus (GDM). Urinary antimony concentrations in women with GDM were significantly higher than those in women without GDM. Antimony exposure correlates with increased risk of GDM during early pregnancy.